2018
DOI: 10.2175/106143017x15054988926299
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient Removal from Wastewater Using Microalgae: A Kinetic Evaluation and Lipid Analysis

Abstract: The objective of this study was to examine the performance of mixed microalgal bioreactors in treating three different types of wastewaters-kitchen wastewater (KWW), palm oil mill effluent (POME), and pharmaceutical wastewater (PWW) in semi-continuous mode and to analyze the lipid content in the harvested algal biomass. The reactors were monitored for total nitrogen and phosphate removal at eight solid retention times (SRTs): 2, 4, 6, 8, 10, 12, 14, and 16 days. The nutrient uptake kinetic parameters were quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…POME has been successfully used to cultivate Chlamydomonas sp. [11], Chlorella sorokiniana [12], Botryococcus brauni [13], and a mixed culture of microalgae [14]. However, Kayombo et al, in 2003, reported that a higher concentration of POME would inhibit microalgae growth due to its biotic and abiotic factors.…”
Section: Introductionmentioning
confidence: 99%
“…POME has been successfully used to cultivate Chlamydomonas sp. [11], Chlorella sorokiniana [12], Botryococcus brauni [13], and a mixed culture of microalgae [14]. However, Kayombo et al, in 2003, reported that a higher concentration of POME would inhibit microalgae growth due to its biotic and abiotic factors.…”
Section: Introductionmentioning
confidence: 99%
“…The data used for calibration and validation covers a diverse set of input parameters for Carbon (C), Nitrogen (N), Phosphorus (P), light (I) and temperature (T). For cost estimation, feed water concentrations of kitchen wastewater in the Indian Institute of Technology (IIT) Hyderabad (IITH) are taken from (Babu et al 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Some algal species can release these organic compounds under normal conditions, some in response to low nutrient stress or other stressful conditions (e.g., unfavorable light, pH, or temperature), and during the decay of algal cells (Villacorte et al, 2015). The reactors with pure algal consortium showed an increment in effluent organic carbon and nutrient concentrations (Babu et al, 2018;. According to the literature, the C/N ratio of 6:1 was reported as the optimal value for the highest nutrient removal for algal-bacterial culture in domestic wastewater treatment (Xu et al, 2017;Yan et al, 2012).…”
Section: Biomass On Sponge Mediamentioning
confidence: 99%